O USO DAS CAE (ENGENHARIA ASSISTIDA POR COMPUTADOR) NO ENSINO DE ANÁLISE ESTRUTURAL, PARA CURSOS DE GRADUAÇÃO EM ENGENHARIA - Martins, Gustavo Cardoso (2023)
The curricular components of engineering courses are developed with the expectation that the content taught in the classroom will be able to produce in students the ability to administer all the theoretical and practical material necessary for the academic training of engineering professionals. However, the educational context in Brazil is less ideal, and what is observed are excessively abstract curricular matrices, with tiresome and rigid approaches that cause, among other things, alarming rates of failure and evasion in engineering schools. On the other hand, the use of digital tools in engineering teaching has made it possible to correct part of this educational mismatch, as is the case with CAE (Computer Aided Engineering) augmented reality simulators. With this background in mind, this master's thesis study studied the learning development of students in the 9th and 10th period of Civil and Mechanical Engineering courses during the joint use of the CYPE 3D software in the Structural Analysis discipline. All research was based on the learning preferences identified in the Felder-Silverman Model. Thus, it was possible to recognize the sensorial-visual predictions of the students who participated in the research, and to conclude that the use of the CAE augmented reality application during the teaching of Structural Analysis, led the newly acquired information to progress towards understanding, in Richard Felder's terms.